Factors affecting students’ achievement in Mathematics: case study in Terengganu / Nazuha Muda@Yusof, Zokree Abdul Karim, Ruzaidah A. Rashid and Zamzulani Mohamed - Muda@Yusof, Nazuha; Abdul Karim, Zokree; A. Rashid, Ruzaidah; Mohamed, Zamzulani (Universiti Teknologi MARA, Perlis, 2019)
Most programs at the university level require completion of mathematics courses. To survive in university, those who are taking mathematics courses should succeed in their examination so that this can be a path for them to proceed smoothly in their study. This research investigates the factors contributing towards achievement in mathematics at a public university. The identified factors are students’ attitude, student-centered learning and classroom environments. The data was collected randomly from 86 students who took business mathematics course in 2018 through a distribution of questionnaires. This study focused on the measurement model and structural model of Partial Least Square analysis. The findings indicate that students’ attitude most significantly affected the achievement in mathematics, followed by students’ centered learning. Meanwhile, classroom environment is found as an insignificant factor of the achievement in mathematics. As a conclusion, students’ attitude is the most influential factor in mathematics achievement compared to students’ centered learning and classroom environments. Therefore, the management of higher education should focus on the empowerment of students’ attitude towards mathematics subject and improve the quality of student-centered learning at the university.